Proceedings of the 5th Universitas Ahmad Dahlan Public Health Conference (UPHEC 2019) 2020
DOI: 10.2991/ahsr.k.200311.043
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Junior-High-School Children in Bogor, Indonesia, Related to Climate Change Health Impacts

Abstract: Sustainable Development Goals require the capacity for resilience and adaptation to climate-related disasters to be strengthened. This capacity is fundamental in healthy city development, which also highlights the importance for youth to have it as early as possible. Therefore, it is crucial to understand their current state before building their capacity. This study aims at measuring the level of knowledge and attitude of junior-high-school students in Bogor City, West Java Province, Indonesia, on health impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Furthermore, the current study found no significant association between knowledge of climate change and climate-friendly dietary choices. This finding was consistent with a Finnish study that reported a good knowledge of climate change was not associated with climate-friendly dietary choices because knowledge is not always translated into a positive attitude (Korkala et al, 2014;Puspita et al, 2020). Conversely, a Malaysian study reported that knowledge was a predictor of behavioral intention toward the consumption of climate-friendly foods (Shariff et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Furthermore, the current study found no significant association between knowledge of climate change and climate-friendly dietary choices. This finding was consistent with a Finnish study that reported a good knowledge of climate change was not associated with climate-friendly dietary choices because knowledge is not always translated into a positive attitude (Korkala et al, 2014;Puspita et al, 2020). Conversely, a Malaysian study reported that knowledge was a predictor of behavioral intention toward the consumption of climate-friendly foods (Shariff et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…The questions about knowledge of climate change were adopted from previous studies (Sulistyawati et al, 2018;Kause et al, 2019;Puspita et al, 2020). This part consisted of 56 items whereby one (1) point was given for each correct answer and zero (0) point was given for the wrong answer.…”
Section: Knowledge Of Climate Changementioning
confidence: 99%
See 3 more Smart Citations